Entrepreneurship and the Business Environment in Africa: An Application to Ethiopia - Zuzana Brixiova; Mthuli Ncube (Institute for the Study of Labor (IZA), 2013)
Since mid-2000s, Ethiopia has been one of the fastest growing countries in the world. However, productive entrepreneurship in high-value added activities has made limited contributions to this growth, in part because of a weak business environment. Moreover, the low-productive firms in the informal sector still account for a large share of employment. Reflecting these facts, this paper presents a model of costly entrepreneurial start-ups in an economy with a large informal sector and rigid business environment where an equilibrium outcome can be a low-skill, low-productivity trap. By fostering productive start-ups and skilled employment, creation of an enabling business environment could help move the Ethiopian economy into high-productivity equilibrium.
Keywords: L26; J24; J48; O17; 330; entrepreneurship; SME start-ups; low productivity trap; multiple equilibria; Africa